The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1002/ente.201300085
|View full text |Cite
|
Sign up to set email alerts
|

Graphene‐Based Flexible Micrometer‐Sized Microbial Fuel Cell

Abstract: Microbial fuel cells harvest electrical energy produced by bacteria during the natural decomposition of organic matter. We report a micrometer‐sized microbial fuel cell that is able to generate nanowatt‐scale power from microliters of liquids. The sustainable design is comprised of a graphene anode, an air cathode, and a polymer‐based substrate platform for flexibility. The graphene layer was grown on a nickel thin film by using chemical vapor deposition at atmospheric pressure. Our demonstration provides a lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…The main substrates used in graphene production are transition metal materials, e.g., Cu [72] and Ni [7]. The graphene films obtained can be transferred to other substrates, maintaining their excellent conductivity and transmittance.…”
Section: Synthesis Methods Of Graphene-modified Electrodesmentioning
confidence: 99%
See 2 more Smart Citations
“…The main substrates used in graphene production are transition metal materials, e.g., Cu [72] and Ni [7]. The graphene films obtained can be transferred to other substrates, maintaining their excellent conductivity and transmittance.…”
Section: Synthesis Methods Of Graphene-modified Electrodesmentioning
confidence: 99%
“…Chemical vapor deposition (CVD) is a widely applied technique for manufacturing semiconductor films, where the chemical reaction of a carbon source (e.g., methane [ 69 ], ethanol [ 70 ], and cyanuric chloride [ 71 ]) is conducted in a high-temperature, high gas flow rate condition and the resultant film is deposited on the surface of a heated solid substrate. The main substrates used in graphene production are transition metal materials, e.g., Cu [ 72 ] and Ni [ 7 ]. The graphene films obtained can be transferred to other substrates, maintaining their excellent conductivity and transmittance.…”
Section: Synthesis Methods Of Graphene-modified Electrodesmentioning
confidence: 99%
See 1 more Smart Citation
“…The rise of graphene within the recent years had of course also an impact on the research of carbon‐material‐based MFC. Graphene and its derivatives (graphene oxide (GO), reduced graphene oxide (r‐GO), functionalized graphene and so on), exhibit outstanding chemical and physical properties, including mechanical robustness, good electron conductivity, high surface area and suitable bioadhesive properties, which make them highly promising candidates for anodes in MFCs . Initially, r‐GO‐modified carbon‐cloth electrodes were studied and it was shown that the anodes biofilm formation and conductivity was increased after the modification with r‐GO .…”
Section: Carbon‐based Electrodes In Mfcsmentioning
confidence: 99%
“…Instead of using the physical coating method, Liu and coworkers [18] adopted an electrochemical method, in which GO was electrophoretically transported to the surface of a carbon cloth (CC) electrode in a two-electrode cell under 0.3 mA cm −2 anodic current and then reduced to GNSs under 0.6 mA cm −2 cathodic current; in that way, they determined the optimal deposition time that gave the best performance of the MFC. wastewater, indicating the potential application of GNSs for lab-on-a-chip MFC devices [26]. As a typical flat-sheet material, GNSs applied to an anode electrode tend to stack as a result of the strong van der Waals attraction between the sheets during the coating process, thereby compromising their high accessible surface area.…”
Section: Graphene Nanosheetsmentioning
confidence: 99%